Pengaruh Bimbingan Kelompok Terhadap Perilaku Asertif Siswa Di SMP Srijaya Negara - Rani Mega Putri; Tri Wahyuni (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2018)
This study aims to determine the influence of group guidance on student assertive behavior in SMP Srijaya Negara Palembang. The population in this study is all students of class VII which amounted to 72 students and the sample amounted to 8 students who have low assertive behavior. The research method used is One Group Pretest-Posttest Design experiment and treatment given 3 times meeting with group guidance service. Data collection techniques used questionnaires or questionnaires. Data analysis technique using t test formula (t-test). Pre-test results showed 8 students who were subjected to the study obtained an average assertive behavior score of 98.62 included in the low category. After being given treatment or treatment of post-test result showed assertive behavior score of 8 students in high category that is average 141,75. From the results of data analysis obtained t count = 14,61 and ttable in significant level 5% that is 2,365, so that known that t count is bigger than ttable or 14,61> 2,365. It can be concluded that there is influence of group guidance on student assertive behavior in SMP Srijaya Negara Palembang.